2011
DOI: 10.1007/s00428-011-1079-9
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation profile during multistage progression of pulmonary adenocarcinomas

Abstract: Multiple genetic and epigenetic alterations are known to be involved in the carcinogenesis of peripheral pulmonary adenocarcinoma (ADC). However, epigenetic abnormalities have not been extensively investigated in the following multistage progression sequence: atypical adenomatous hyperplasia (AAH) to adenocarcinoma in situ (AIS), to invasive ADC. To determine the potential role of promoter methylation during ADC development of the lung, we examined methylation status in 20 normal, 20 AAH, 30 AIS, and 60 ADC lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 37 publications
1
33
0
1
Order By: Relevance
“…30,31) RAS association domain family gene 1 (RASSF1) is a recently discovered RAS family-related gene that modulates multiple apoptotic and cell-cycle checkpoint pathways and promotes microtubule stability. RASSF1A, one isoform of RASSF1, has been identified as a tumour suppressor gene whose inactivation has been implicated in the development of many cancers, especially lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…30,31) RAS association domain family gene 1 (RASSF1) is a recently discovered RAS family-related gene that modulates multiple apoptotic and cell-cycle checkpoint pathways and promotes microtubule stability. RASSF1A, one isoform of RASSF1, has been identified as a tumour suppressor gene whose inactivation has been implicated in the development of many cancers, especially lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is likely that TMEFF2 methylation could be related to other environmental factors rather than tobacco smoking. Notably, the prevalence of TMEFF2 methylation in NSCLCs is approximately an intermediate value compared with the results of the two groups showing a 72% to 30% frequency in lung ACs (Chung et al, 2011;Suzuki et al, 2005). These discrepancies may be attributable to methodological or geographical differences.…”
Section: Discussionmentioning
confidence: 73%
“…Moreover, TMEFF2 is mapped to human chromosome 2q32.3, where frequent loss of heterozygosity is seen in various human tumors (Beder et al, 2003;Otsuka et al, 1996;Takita et al, 2001) and is frequently hypermethylated in various human cancers (Lin et al, 2011;Suzuki et al, 2005;Young et al, 2001). In particular, chip-based analysis has shown that TMEFF2 gene is identified to have a distinct methylation pattern in nonsmall cell lung cancers (NSCLCs) compared to normal tissues (Field et al, 2005), and TMEFF2 methylation has been reported to frequently occur in the precancerous lesion and early stage of lung adenocarcinoma (AC), such as atypical adenomatous hyperplasia and bronchioloaveolar cell carcinoma (Chung et al, 2011;Selamat et al, 2011). Importantly, aberrantly methylated markers identified in lung tissue samples can be detected in peripheral blood, providing a valuable approach to non-invasive screening for early detection of lung cancer (Bremnes et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…RUNX3 is frequently silenced by DNA hyper-methylation in many cancers, including lung cancer [39][40][41]. RUNX3 methylation correlates with clinical stage and degree of differentiation in NSCLC [42].…”
Section: Discussionmentioning
confidence: 99%